2013
DOI: 10.1371/journal.pone.0073424
|View full text |Cite
|
Sign up to set email alerts
|

TRPP2 and TRPV4 Form an EGF-Activated Calcium Permeable Channel at the Apical Membrane of Renal Collecting Duct Cells

Abstract: ObjectiveRegulation of apical calcium entry is important for the function of principal cells of the collecting duct. However, the molecular identity and the regulators of the transporter/channel, which is responsible for apical calcium entry and what factors regulate the calcium conduction remain unclear.Methods and ResultsWe report that endogenous TRPP2 and TRPV4 assemble to form a 23-pS divalent cation-permeable non-selective ion channel at the apical membrane of renal principal cells of the collecting duct.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 37 publications
(71 reference statements)
2
49
2
Order By: Relevance
“…Therefore, we performed immunofluorescence study in orpk cells to determine the localization of the NHE isoforms in collecting duct cell lines. Similar to a previous report (41), EGFR (green) was predominantly localized in the intracellular compartment and at the basolateral membrane in cilia (ϩ) cells but was apically localized in cilia (Ϫ) cells ( Fig. 2A, yellow arrow pointing apical EGFR).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, we performed immunofluorescence study in orpk cells to determine the localization of the NHE isoforms in collecting duct cell lines. Similar to a previous report (41), EGFR (green) was predominantly localized in the intracellular compartment and at the basolateral membrane in cilia (ϩ) cells but was apically localized in cilia (Ϫ) cells ( Fig. 2A, yellow arrow pointing apical EGFR).…”
Section: Resultssupporting
confidence: 89%
“…We also found that EGFR and NHE-1 were both localized at the apical surface in cilia (Ϫ) cells compared with the cilia (ϩ) cells by immunofluorescence (Fig. 2), which supports findings from previous reports (4,18,41). Interestingly, EGF stimulated NHE activities in cilia (Ϫ) cells compared with cilia (ϩ) cells (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, it has been suggested that TRPP2, present in the primary cilia, can form heterodimers with TRPV4 to function as a mechanosensitive channel. In this regard, TRPV4 has been suggested to be an essential component of the TRPP2-TRPV4 heterodimer (31,69). In fact, depletion of TRPV4 abolishes the ability of renal epithelial cells to sense luminal flow (31).…”
Section: Discussionmentioning
confidence: 99%
“…This flow-mediated increase in cell calcium is diminished if either PC1 or PC2 are absent or nonfunctional (8, 87,150). Recent studies suggest that PC2 forms multimeres with either TRPV4 or with TRPC1, which form cation channels with distinct biophysical properties (2, 65,157). The functional consequences of PC2 partnering with other TRP channels in terms of normal flow-mediated calcium responses or in PKD have yet to be determined.…”
Section: Figure 1 Activation Of Intrarenal Ras In Pkdmentioning
confidence: 99%